1995
DOI: 10.1177/140349489502300203
|View full text |Cite
|
Sign up to set email alerts
|

Diet of Finnish Children in Relation to the Family's Socio-Economic Status

Abstract: The differences between higher and lower socio-economic groups in food consumption, energy intake and nutrient density of the diet of Finnish 9- to 15-year-old children were examined in a study performed within the project entitled Cardiovascular Risk in Young Finns. Data on food consumption were collected using the 48-hour recall method. Family's socio-economic status was defined according to the father's educational level, his occupation, and family income. Children of families with higher socio-economic sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
4
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 14 publications
(8 reference statements)
4
38
4
1
Order By: Relevance
“…However, previously reported low consumption of vegetables and fruit in school children and adolescents from families with a low socioeconomic status (Haapalahti et al, 2003, Laitinen et al, 1995 was not found in the present study.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…However, previously reported low consumption of vegetables and fruit in school children and adolescents from families with a low socioeconomic status (Haapalahti et al, 2003, Laitinen et al, 1995 was not found in the present study.…”
Section: Discussioncontrasting
confidence: 96%
“…However, data on the diet of primary school children are scarce. Moreover, Finnish school children and adolescents from families with a lower socioeconomic status have been suggested to have less healthy dietary factors, such as a lower consumption of vegetables and fruit and a higher consumption of high-fat milk and butter than children from families with a higher socioeconomic status (Haapalahti et al, 2003, Laitinen et al, 1995. However, there are few studies on the association of socioeconomic background of a family with dietary habits of younger school children.…”
Section: Introductionmentioning
confidence: 99%
“…In a Finnish study, the 9-to 15-year-old children of farmers had lower vitamin D intake than the children of the upper and lower white-and blue-collar workers. The children of fathers with less than 9 years of formal education had the lowest intake of vitamin D (Laitinen et al, 1995). In our previous study, the level of parental education was positively associated with the child's vitamin D supplementation at the age of 2 years (Marjamäki et al, 2004).…”
Section: Introductionmentioning
confidence: 73%
“…The variations in vitamin D intake and vitamin D status have been linked to social class (Gregory et al, 1995;Laitinen et al, 1995). In a Finnish study, the 9-to 15-year-old children of farmers had lower vitamin D intake than the children of the upper and lower white-and blue-collar workers.…”
Section: Introductionmentioning
confidence: 99%
“…Ces nourrissons ont également un risque plus élevé d'avoir un petit poids à la naissance, de ne pas être allaités [11][12][13][14] et d'être nourris précocement avec du lait de vache (demi-écrémé, donc riche en protéines), autant de facteurs supposés augmenter le risque d'obésité future [15][16][17]. Les enfants et adolescents de milieux défavorisés sont plus sédentaires [18][19][20][21][22], ils mangent plus souvent devant la télévision [23,24], consomment moins de fruits et légumes en quantité [25,26] et en variété [27], et plus de boissons sucrées [28][29][30][31] que les jeunes issus de milieux aisés. De nombreuses études, souvent menées à l'étranger, mettent en évidence un faible niveau d'activité physique, une forte sédenta-rité [10, [32][33][34][35][36] et des déséquilibres alimentaires prononcés dans les populations adultes de faible SSE (revue de la littérature in [37]).…”
Section: Facteurs Explicatifs Directsunclassified